2019
DOI: 10.1590/s1678-9946201961016
|View full text |Cite
|
Sign up to set email alerts
|

Murine typhus in Mexico City: report of an imported case

Abstract: Murine typhus is endemic in several countries. We herein report an imported case of murine typhus caused by Rickettsia typhi in Mexico City. This is the first report of a case after almost 20 years since the last report. The species was confirmed by DNA sequencing and phylogenetic reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Additionally, measures must be established to reduce people's contact with these species, sometimes used as companion animals, and their fleas; this situation could trigger disease outbreaks. In humans, murine typhus is recognized as an emerging disease in Mexico City (Sánchez‐Montes, et al., 2019b), since there were no records of this disease until year 2000, when an open population serological study demonstrated the presence of antibodies against R. typhi , with a seroprevalence of 30% (Acuna‐Soto et al., 2000). However, the first human case was confirmed in 2015, and the Ministry of Health notified seven cases until 2017 (four women and three men, between 10 to 59 years old, with an incidence rate that goes between 0.01 and 0.03 per 100,000 inhabitants (CENAPRECE, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, measures must be established to reduce people's contact with these species, sometimes used as companion animals, and their fleas; this situation could trigger disease outbreaks. In humans, murine typhus is recognized as an emerging disease in Mexico City (Sánchez‐Montes, et al., 2019b), since there were no records of this disease until year 2000, when an open population serological study demonstrated the presence of antibodies against R. typhi , with a seroprevalence of 30% (Acuna‐Soto et al., 2000). However, the first human case was confirmed in 2015, and the Ministry of Health notified seven cases until 2017 (four women and three men, between 10 to 59 years old, with an incidence rate that goes between 0.01 and 0.03 per 100,000 inhabitants (CENAPRECE, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Murine typhus is a human‐neglected rickettsiosis caused by R. typhi and a common disease in several Latin‐American countries such as Brazil, Colombia and Mexico (Minervino et al., 2020; Sánchez‐Montes, et al., 2019b). Typically, the transmission cycle of R. typhi has been associated with urban cycles that involve rats ( Rattus spp.)…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, as documented in the scientific literature, confirmed and suspected autochthonous human cases have been described in Brazil, 69,73 Mexico, [74][75][76][77][78][79][80] Colombia, [81][82][83][84][85] Nicaragua, 86 and Honduras (Figure 1B). 87 In addition, murine typhus was reported in a young Dutch girl after visiting Suriname (her length of visit and time of symptom onset supported infection while traveling).…”
Section: Contemporary Perspective Of Murine Typhus In Latin Americamentioning
confidence: 99%
“…In Mexico, in addition to serological results, isolation and molecular characterization of R. typhi have been obtained from clinical samples. [75][76][77][78][79] Research on the current ecoepidemiology of murine typhus in Latin America is scarce. In Colombia, studies conducted from 2010 to 2011 and 2015 to 2017 in Caldas Department (considered an endemic area) investigated for the molecular detection of flea-borne rickettsiae in almost 2,800 fleas collected from cats, dogs, marsupials, and synanthropic and wild rodents.…”
Section: Contemporary Perspective Of Murine Typhus In Latin Americamentioning
confidence: 99%
“…When sought by clinicians and researchers, the presence of murine typhus as a reemerging disease entity in South America becomes evident [91]. In North America, cases are recognized in Mexico [92,93] and in the U.S. states of Hawaii, California, and Texas [94][95][96]. There has been an alarming increase in California, with foci around homeless encampments, and in Texas, where the distribution of disease is moving northward [33,96,97].…”
Section: Epidemiology Of An Underrecognized and Reemerging Cause Of I...mentioning
confidence: 99%